2000
DOI: 10.1046/j.1365-2141.2000.01977.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term survival of infants with idiopathic myelofibrosis

Abstract: Summary. Idiopathic myelofibrosis can develop in children as well as adults. However, the disease appears to be much more aggressive in adults, being characterized by poor survival rates and a high frequency of malignant transformation. Here, we describe three cases of idiopathic myelofibrosis in infants, two of whom were followed for 16 and 22 years after diagnosis. Neither of these patients required more than minimal supportive care, and both have had spontaneous erythropoietic recovery as early as 2± 3 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 17 publications
1
25
1
1
Order By: Relevance
“…However, in a small number of patients (10%), the disease is diagnosed before age 40 years (5). MMM has also been described in children where it seems to have a more benign course (6). Disease incidence is estimated from 0.5 to 1.5 per 100,000 population per year although the incidence may be higher in Ashkenazi Jews (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…However, in a small number of patients (10%), the disease is diagnosed before age 40 years (5). MMM has also been described in children where it seems to have a more benign course (6). Disease incidence is estimated from 0.5 to 1.5 per 100,000 population per year although the incidence may be higher in Ashkenazi Jews (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…rickets • hypocellular MDS Many cases presenting in infancy may eventually 'burn out', with spontaneous erythropoietic recovery occurring as early as 2-3 years after diagnosis (Altura et al, 2000). Therefore, a conservative approach is recommended for such patients and a trial of steroids should be considered, once AMKL and rickets (Bhakhri & Debata, 2010) have been excluded.…”
Section: Pmf In Childhoodmentioning
confidence: 99%
“…Indeed, a normal karyotype is characteristic of paediatric patients and, because of their better prognosis, may indicate both a different pathogenesis and the need for a more conservative management. 159 Two recent reports from the Mayo Clinic, one retrospective 28 and the other prospective, 160 have suggested that not all cytogenetic abnormalities are associated with an adverse prognosis in PMF. For example, they reported that the commonest abnormalities, namely13qÀ and 20qÀ, may have little impact on survival, in contrast to trisomy 8 and 12qÀ which were independent prognostic determinants, together with age and anaemia, of an inferior outcome.…”
Section: Cytogenetics and Prognosismentioning
confidence: 99%